Pengaruh Pengetahuan dan Kesadaran SDM Terhadap Sikap Dalam Upaya Penanggulangan Pencemaran di Perairan dan Pelabuhan - Pranyoto Pranyoto; Prapti Utami; Umi Kholifah (Dinamika Bahari, 2022)
The increase in shipping activities as triggers an increase in the risk of marine pollution. Over the last few years, several cases have been found that trigger environmental pollution in the sea and coast. In an effort to protect the environment, the goverment needs to take clear and firm steps to socialize various regulations related to environmental protection efforts. One of regulations related the efforts to protect the marine and coastal environment is the Minister of Transportation Regulation Number PM 58 in 2013 concerning the prevention of pollution in water and ports. Also MARPOL 1973/1978. The purpose of this study is to analyze the influence of knowledge and awareness of human resourcesch on attitudes in efforts to control pollution in water and ports. Qualitative survey method data was used the Reseach approache, processed using analysis techniques and recording interactions and in-depth interviews. The results of this study indicate that the awareness of operators and personnel of law enforcement officers from marine and coastal guard units in increasing understanding of various regulations governing efforts to control pollution in waters and ports is very high. This research concludes that knowledge and awareness of human resources affect the attitude of human resources to try to do various pollution prevention in waters and ports.